Creativity, community, & growth: A social geography of urban craft beer - Neil Reid; Jay D. Gatrell (REGION, 2017)
To better understand the non-economic drivers of growth in emerging industries, this paper examines the craft beer industry. Specifically, the paper will review two examples-the Black Cloister Brewing Company in Toledo, OH and 3rd Turn Brewery, Louisville, KY-to understand how the values of entrepreneurs and local firms that are situated at the nexus of work, place, and creativity promote growth. Further, the paper will consider the socio-cultural meaning of creativity relative to the craft beer industry and the many ways in which the concept of innovation traditionally used by economic geographers to understand growth can be better understood within the context of creativity in some industries. In doing so, the paper represents a conceptual shift away from innovation towards creativity, as well as community.
Keywords: 330